A Review of Palm Oil Valorization Technologies - Loso Judijanto (Malikussaleh University, Aceh, Indonesia, 2025)
The accelerating expansion of palm oil cultivation has triggered a substantial rise in the volume of biomass waste, notably empty fruit bunches (EFB), palm kernel shells (PKS), and palm oil mill effluent (POME), which pose environmental challenges if unmanaged. In response to growing sustainability concerns, this study explores how technological innovations have enabled the valorization of palm oil waste streams within the framework of the circular economy (CE). This research aims to identify and evaluate the range of technologies developed to convert palm-based waste into value-added products and assess their comparative performance in terms of scalability, environmental benefits, and CE alignment. This study adopts a qualitative research approach using the Systematic Literature Review (SLR) method, structured according to the PRISMA protocol. Data were collected through a focused search on the ScienceDirect database using refined Boolean combinations relevant to CE, palm oil biomass, and valorization technologies. A multi-stage screening process involving relevance, article type, publication year (2021–2025), and open-access availability yielded 37 peer-reviewed research articles for in-depth analysis. Data were analyzed thematically and synthesized qualitatively. Findings reveal a diversification of valorization pathways, including anaerobic digestion, pyrolysis, hydrothermal liquefaction, nanomaterial extraction, and catalytic upgrading, each offering distinct advantages and trade-offs. Technologies varied significantly in scalability, environmental impact, and their contribution to CE objectives. The review concludes that integrated and decentralized valorization systems hold great promise for closing resource loops and reducing emissions. Future research should focus on region-specific lifecycle assessments and the techno-economic feasibility of hybrid technologies.